S2 Multi-drug Resistant Tuberculosis (MDR-TB) treatment in the UK: a survey of injectable use and toxicity in practice. (16th November 2010) - Sturdy, A; Goodman, A; José, R J; Loyse, A; O'Donoghue, M; Kon, O M; Dedicoat, M J; Harrison, T; John, L; Lipman, M; Cooke, G
Abstract : Rationale: Recent discoveries in human genetics have identified mitochondrial mutations which confer a high risk of sensorineural deafness in individuals exposed to aminoglycosides. Successful MDR-TB treatment often requires prolonged use of these agents. There are little data from the UK to inform the use of genetic tests within MDR-TB patients. We set out to survey MDR-TB practice in the UK with an emphasis on injectable drug use, ototoxicity and audiological monitoring practice. Methods: Five centres took part in a retrospective study of patients initiating injectable treatment for MDR-TB between 1 January 2004 and 31 December 2009. Data were collected regarding patient characteristics, choice of injectable, methods and frequency of ototoxicity screening and incidence of drug-related complications. Results: Treatment for 50 MDR-TB patients was reviewed. 29/50 (58%) patients received amikacin, 11/50 (22%) capreomycin, 4/50 (8%) streptomycin and 6/50 (12%) more than one injectable. Three centres used amikacin as their preferred injectable, two used capreomycin. Audiological screening for ototoxicity was variable. 21/50 (42%) patients received baseline screening within 2 weeks of starting an injectable. 16/50 (32%) patients went on to have monthly audiograms, with the majority screened more infrequently or if symptoms were reported. 12/50 (24%) patients received no screening at any point. Ototoxicity was defined as a 20 dB loss from baseline on audiogram at one test frequency, or a 10 dB loss at two adjacent frequencies, or in the absence of a baseline result, as two or more frequencies below 20 dB. If no audiograms were available, the definition was symptomatic. 14/50 (28%) of patients experienced ototoxicity, with 9/50 (18%) left with persistent hearing loss. Increased age (p=0.02), use of amikacin (p=0.02) and decreased renal function on therapy (p=0.01) were significantly associated with ototoxicity (see Abstract S2 Table 1 ). No centre routinely tests for mitochondrial DNA mutations. Conclusions: There is local variation in both choice of injectable agent and in ototoxicity screening practices between the MDR treatment centres studied. The data suggest capreomycin might be associated with less ototoxicity when compared to amikacin. There are no UK guidelines to inform best practice and better evidence, including clinical and cost-effectiveness studies, is needed to inform the implementation of current technology including genetic testing.